Low HDL cholesterol is associated with elevated TNFR1 and TNFR2 levels in early diabetic kidney disease - Su, Jianfang; Su, Jing; Wang, Wei; Pan, Jie; Zhang, Xianhui (Frontiers in Endocrinology, 2026)
BackgroundEarly diabetic kidney disease (DKD) remains difficult to diagnose accurately since microalbuminuria lacks sensitivity and specificity. Tumor necrosis factor receptors (TNFRs), especially TNFR1 and TNFR2, have emerged as potential markers of renal inflammation and injury. Dyslipidemia, particularly reduced high-density lipoprotein cholesterol (HDL), is associated with the inflammatory milieu in type 2 diabetes mellitus (T2DM).ObjectiveTo investigate the association of serum TNFR1 and TNFR2 with early renal injury in T2DM and to determine the impact of HDL on TNFRs levels.MethodsA cross-sectional study was conducted in 258 T2DM patients (135 with normoalbuminuria, 123 with microalbuminuria) and 100 age- and sex-matched healthy controls. Serum TNFR1, TNFR2, lipid profile, fasting blood glucose (FBG), and estimated glomerular filtration rate (eGFR) were measured. Group differences were analyzed, and correlation and multivariable regression analyses were performed to identify determinants of TNFR levels.ResultsBoth TNFR1 and TNFR2 were significantly higher in patients with microalbuminuria compared with healthy controls (P < 0.001). TNFR1 levels increased progressively from healthy controls to normoalbuminuric and microalbuminuric groups, showing the strongest associations with UACR, eGFR, diabetes duration, and HDL. In multivariable regression, HDL emerged as the most significant negative predictor of both TNFR1 and TNFR2, independent of glycemic measures and other metabolic factors. Age was also independently associated with higher TNFR concentrations.ConclusionSerum TNFR1 and TNFR2 are a sensitive biomarker for early renal injury in T2DM. Importantly, low HDL is independently associated with elevated TNFR1 levels, suggesting that lipid metabolism, beyond glucose control, plays a critical role in DKD progression. Monitoring HDL levels and targeting dyslipidemia may aid in the early prevention and intervention of DKD.